1999
DOI: 10.1038/sj.onc.1202530
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage-dependent expression of cyclin A in primary cells requires a negative DNA regulatory element and a functional Rb

Abstract: Many cells, when cultured in suspension, fail to express cyclin A, a regulatory component of cell cycle kinases cdc2 and cdk2 and as a consequence, do not enter S phase. However, many cell type-speci®c di erences are disclosed between not only normal and transformed cells, but also between cell lines whose proliferation is strictly anchorage-dependent. These apparent discrepancies are seen in established cell lines most probably because of adaptative events that have occurred during cell culture. We have there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Pocket proteins are thought to regulate cyclin A promoter activity through the CDE/CHR site (18,28,29,32,33), but the proteins that bind to this site are very poorly defined. Some studies (32,44) suggest that the CDE is occupied by E2F4/p107 complexes, but the binding of any E2F to the cyclin A promoter is highly controversial (see the introduction).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pocket proteins are thought to regulate cyclin A promoter activity through the CDE/CHR site (18,28,29,32,33), but the proteins that bind to this site are very poorly defined. Some studies (32,44) suggest that the CDE is occupied by E2F4/p107 complexes, but the binding of any E2F to the cyclin A promoter is highly controversial (see the introduction).…”
Section: Discussionmentioning
confidence: 99%
“…However, another group reported that E2Fs do not bind with high affinity to the CDE site in the cyclin A promoter (18), and a third group (21) reported that E2F1 and 3, but not E2F4, bind to the CDE and act as transcriptional activators at G 1 /S rather than repressors at G 0 and early G 1 . Moreover, experiments with pRb-null and p107-null mouse embryo fibroblasts (MEFs) emphasize that pRb, and not p107, is important for cyclin A gene expression (28,29). Thus, the exact mechanism by which pocket proteins control cyclin A gene expression through the CDE/CHR is poorly understood and may well involve both indirect and direct effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclin A mRNA and protein accumulations at the end of G 1 are required for progression into S phase and DNA replication (15,29,45). We have previously analyzed the expression of cyclin A in human and rodent cells (1,2,(30)(31)(32)(33) and identified functional DNA sequences present in the mouse cyclin A promoter (2,21). In vivo genomic dimethyl sulfate footprinting revealed the presence of cell cycle-regulated protein binding elements close to the major transcription initiation sites.…”
Section: E4fmentioning
confidence: 99%
“…When deprived of an ECM anchorage, cells arrest in G 1 phase with inactive Cdk4/6 and Cdk2 due largely to repression of the cyclin D1 and cyclin A genes and induction of p27 KIP1 (15)(16)(17)(18). Inactivation of CDK4 and CDK6 activates retinoblastoma protein (RB) and its cognates, which in turn bind and thereby inactivate the E2F-DP transcription factor complexes, shutting down a subset of genes essential or important for the onset of S phase, including Cdc6, cyclin A, E2F1, and Emi1 (19 -23).…”
mentioning
confidence: 99%